ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKUNTANSI KEUANGAN PADA TOKO SARI BAROKAH DENGAN MENGGUNAKAN SOFTWARE BORLAND DELPHI 7.0 - WAHYUNING, SRI (STEKOM, 2011)
All human activity requires a rapid and accurate information. Current information systems play animportant role in the development and progress, especially in the corporate world. Humans arerequired to be able to get the job done efficiently, quickly and on time. With the implementation ofa computerized financial accounting system appropriate for an agency or company and will supportthe smooth progress of the company. An example is the problem that occurred in Sari Barokahwhich location Jl.Ngaliyan in Semarang. In conducting its activities are not maximized. Dataprocessing system using a program from Microsoft Office applications. Customer data and supplierdata is not recorded in detail, data purchase and sales data stored in the form of a memorandumrecords, data accounts payable and data is difficult to know with certainty, the financial statementsprepared each end of the month so that the head must wait for the end of the month to find out thecompany’s financial condition. Of the problems mentioned above can be concluded that the maincause of problems that occur in Sari Barokah stores are due to data processing still using manualsystems, and new end of each month to prepare financial statements using the Microsoft office, thepaper relies on data archiving, and therefore caused the damage or loss of data . The system is atthe start of the process input customer data, supplier data, data items, data sales and purchasetransactions, journalizing, and reporting. Expected with the use of this system will be able to speedup the processing of data, minimizing the error rate, save energy and costs.Keyword : Analisa, System, Borland Delphi